Growth of void-free Cu2ZnSn(S, Se)4 thin film by selenization Cu2ZnSnS4 precursor film from ethylene glycol-based solution. (September 2015) - Wen, Qing-Yao; Li, Yan; Yan, Jian-Jun; Wang, Jian; Wang, Cheng-Wei
Graphical abstract: Highlights: A novel, nontoxic ethylene glycol-based solution method is designed for CZTSSe films. A uniform, compact, large and void-free grain size CZTSSe films was obtained. The CZTSSe films has good electrical photoelectric properties. It may hold the promise to further fabricate thin film solar cells. Abstract: Solution method is promising in fabricating Cu2 ZnSn(S, Se)4 (CZTSSe) thin-film solar cells, which could be economical and large-scale implementation, but highly toxic solvents have generally been involved. In this work, an ethylene glycol-based precursor solution method, which is simple and environmentally friendly, was newly designed for fabricating CZTSSe films. It was found that ethylene glycol was a suitable solvent for preparing CuZnSnS4 (CZTS) precursor film, which would be conducive to further applied in selenization processing at moderate temperatures (450 °C, 500 °C, 540 °C). The effects of the selenization temperature on the microstructure, phase composition and photoelectronic properties of CZTSSe films were also investigated. The results reveal that the quality of CZTSSe films could be effectively promoted by selenization temperature, and the highly-crystallized and void-free CZTSSe films were obtained at 540 °C, which may hold the promise for fabricating thin film solar cells.